Nekotorye itogi issledovanij fiziologiceskoj adaptacii v sporte - Solodkov, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
During last 20 years employees of faculty of physiology P.F. Lesshaft's SPbSUPC studied features of physiological mechanisms and laws of adaptive processes at athletes of different specializations to physical loadings. For these years it has been surveyed more than 3000 person. The established laws of adaptation are successfully realized in improvement of adaptive processes of athletes in extreme conditions of their activity about what there is a patent of the Russian Federation for the invention.